Didymodon cordatus Jur. (Pottiaceae), new to the moss flora of China (Bangladesh Journal of Plant Taxonomy, 2013)
Not available.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17402Bangladesh J. Plant Taxon. 20(2): 259-261, 2013